Pengembangan Lembar Kerja Siswa (LKS) Berbasis Kontekstual Dilengkapi Glosarium pada Materi Perubahan Iklim untuk Meningkatkan Hasil Belajar Siswa - Ellys Luthfi Adriyani1; Tabitha Sri Hartati Wulandari2 (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Media in learning, one of them is LKS. The LKS should contain a summary of material contains to improve students understanding, but in reality LKS of IPA materials currently used is not sufficient to improve students understanding. The result observation at SMP Muhammadiyah 13 Kalen Lamongan indicates that LKS used has many deficiencies, that is not presented in contextual, difficult language to understand, unattractive images and lack of explantion of difficult word meaning especially climate change material. This resulted in low students learningmotivation and impact of decreased learning outcomes. Efforts to cope with the development of LKS. This research is aimed to develop LKS based contextual with glossary of climate change material to improve students to be valid, practical, and effective. This research is a research development with R & D method (Research and Development), and use model development of ADDIE (Analyze, Design, Development, Implementation, Evaluation). The result of LKS development showed valid 79,89%, practicality 70% with practical criteria, 93,3% completeness of study result with very high criteria, student response result gets percentage average 98,5% with criterion very effective, and N-gain analysis result is 0.5 with medium criterion. In conclusion, the development of LKS is considerad feasible to be used as a learning media for students.